"More is Different:" Synergistic Effect and Structural Engineering in Double‐Atom Catalysts. (16th November 2020) - Ying, Yiran; Luo, Xin; Qiao, Jinli; Huang, Haitao
Abstract: Double‐atom catalysts (DACs) have emerged as a novel frontier in heterogeneous catalysis because the synergistic effect between adjacent active sites can promote their catalytic activity while maintaining high atomic utilization efficiency, good selectivity, and high stability originating from the atomically dispersed nature. In this review, the recent progress in both experimental and theoretical research on DACs for various catalytic reactions is focused. Specifically, the central tasks in the design of DACs—manipulating the synergistic effect and engineering atomic and electronic structures of catalysts—are systematically reviewed, along with the prevailing experimental, characterization, and computational modeling approaches. Furthermore, the practical applications of DACs in water splitting, oxygen reduction reaction, nitrogen reduction reaction, and carbon dioxide reduction reaction are addressed. Finally, the future challenges for DACs are summarized and an outlook on the further investigations of DACs toward heterogeneous catalysis in high‐performance energy and environmental applications is provided. Abstract : Double‐atom catalysts (DACs) have emerged as a new frontier of heterogeneous catalysis with promoted catalytic activity from the synergistic effect between adjacent active sites. Manipulating the synergistic effect and engineering atomic and electronic structures of catalysts are central tasks in the design of DACs. In this review, experimental and theoretical approaches and practical applications are introduced.